2021
DOI: 10.1007/s42729-021-00501-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Type on Grapefruit and Shaddock Essential Oils

Abstract: Grapefruit and shaddock essential oils (EOs) have remarkable biological activities. Soil types are characterized by various properties which affect the essential oils of grapefruit and shaddock. Many Citrus species are cultivated in the Nile Valley of Egypt, which is characterized by its clay soil, but there are no large areas cultivated with both grapefruit and shaddock. The reclaimed desert in Egypt which characterized by sand soil is expanded by planting many Citrus species, which produce different residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The high sand content in the soil caused an increase in the essential oil ratio and yield (location B) and these results are similar to other studies, which showed that soil stress conditions like high pH, drought, low nutrients, sand, and salinity caused an increase in essential oil ratios [ 42 44 ]. Likewise, Aboukhalid et al [ 45 ] reported that the quality of essential oils was affected by soil structure.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The high sand content in the soil caused an increase in the essential oil ratio and yield (location B) and these results are similar to other studies, which showed that soil stress conditions like high pH, drought, low nutrients, sand, and salinity caused an increase in essential oil ratios [ 42 44 ]. Likewise, Aboukhalid et al [ 45 ] reported that the quality of essential oils was affected by soil structure.…”
Section: Resultssupporting
confidence: 88%
“…Aziz et al [ 46 ] and Said-Al Ahl et al [ 47 ] also observed that essential oil components ratio of Thymus vulgaris L. were higher when cultivated in loamy soil than in clayey soil. Khalid and Ahmed [ 44 ] had also similar results on citrus plants. In this study, it was also claimed that when the amount of sand increased, the essential oil ratio and yield also increased.…”
Section: Resultsmentioning
confidence: 59%
“…One of the factors that can be very involved in this field is the type of weather and region (Figueiredo et al, 2008;Mehalaine et al, 2021). Soil characteristics are influential in this field, and in rich soils, the number and variety of secondary compounds is greater (Khalid & Ahmed, 2021). These factors have significant effects on the quality and quantity of plant essential oils.…”
Section: Introductionmentioning
confidence: 99%